Острів Березань — філія заповідника «Ольвія». Деякі підсумки і перспективи археологічних досліджень - Назаров, В.В. (Археологія, 2001)
У статті наведено основні підсумки археологічних досліджень, що проводилися Березанською експедицією Інституту археології НАН України протягом 1982—2000 рр. Розглянуто перспективні напрями подальших досліджень з урахуванням сучасного статусу острова Березані як філії історико-археологічного заповідника «Ольвія». В статье представлены основные результаты археологических исследований, проведенных на острове Березань в период с 1982 по 2000 г. Березанской экспедицией ИА НАН Украины. Работы велись на разных участках территории античного поселения с целью поиска его границ и определения функциональной специализации отдельных районов. Открыт и исследован архаический культовый комплекс — святилище Афродиты, включающий в себя ограду священного участка, алтарь и небольшой антовый храм. Исследованы остатки жилых построек разных периодов существования поселения, а также остатки каменной постройки римского времени, по-видимому, имевшей функциональную связь со святилищем Ахилла Понтарха. Санкт-Петербургским отрядом, работающим в составе экспедиции, был открыт бронзолитейный комплекс архаического времени. В результате подводных исследований определены границы разрушенной морем части античного поселения; полученные данные позволяют утверждать, что в первые века н. э. территория Березани еще не была островом. В связи с включением территории острова Березань в состав историко-археологического заповедника «Ольвия» экспедиция выполняет комплекс консервационно-реставрационных мероприятий с целью создания в дальнейшем натурной экспозиции, представляющей основные этапы существования города Борисфена. Задачи музеефикации территории острова предполагается учитывать при планировании дальнейших археологических исследований. The article presents the main results of the archaeological investigations, which were held on the island of Berezan from 1982 to 2000 by the Berezan expedition of IA NASU. The works were held on the different plots of the territory of the antique settlement to search its borders and determine the functional specialization of the separate districts. At the same time, there were opened and investigated the archaic cult complex — Aphrodite’s sanctuary, including the fence that surrounded the sacred plot, the altar, and a small antic temple. There were also investigated the remnants of dwelling buildings from different periods of settlement life and the remnants of a stone building of Roman times, which probably had a functional connection with the sanctuary of Achilles Pontarch. A bronze-founding complex from the archaic period was discovered by the Saint-Petersburg detachment of the expedition. Following the underwater investigations was the determination of the borders of the ruined by-the-sea part of the antique settlement. The data demonstrates that in the first centuries AD, Berezan wasn’t an island. In connection with the inclusion of the Berezan’s territory into the composition of the historic-archaeological preserve “Olbia” the expedition adopted the complex of measures on conservation and restoration, to create the location exposition, and represent the basic life stages of the town of Boristhen. The tasks of museumification of the territory of the island will be taken into consideration during the planning of further archaeological investigations.